Keterlaksanaan Penilaian Kompetensi Keterampilan Pada Pembelajaran Matematika Berdasarkan Kurikulum 2013 - Dewanti, Sintha Sih (Pendidikan Matematika Universitas PGRI Yogyakarta, 2018)
This study aims to describe: 1) teachers' understandings of skill competency assessment; 2) the application of skills competency assessment in mathematics learning; and 3) teachers' problematics in applying skills competency assessments. This research used the qualitative approach with descriptive research type. The study was conducted in the academic year 2017/2018 and implemented in 9 junior high schools / Islamic junior high schools in the DIY region. Research subjects were 11 mathematics teachers who are selected using purposive sampling technique. The data collected through structured interviewing methods, observation, and documentation. The data were analyzed by using inductive logic, from the particular to the general. The results show that: 1) teachers' understandings of skills competency assessment are quite good. Teachers understood the various instruments and assessment techniques but have not understood the assessment rubric used in each instrument yet; 2) the application of skills competency assessment has already done well but some were still constrained and have not accorded to the assessment standards; 3) teachers' problematics in applying skill competency assessment are: problems of understanding skill competency assessment, time, administrative complexity, student condition, assessment planning including the development of instrument and assessment rubric, and the implementation of skill competency assessment.Keywords: assessment execution, skill competency assessment, Curriculum 2013